Birth prevalence of cryptorchidism and hypospadias in northern England, 1993–2000. Issue 7 (1st December 2006) - Abdullah, N A; Pearce, M S; Parker, L; Wilkinson, J R; Jaffray, B; McNally, R J Q
Abstract : Aim: There is much debate as to whether the prevalence rates of cryptorchidism and hypospadias are increasing. To address this issue we investigated the birth prevalence of cryptorchidism and hypospadias in the northern region of England during the period 1993–2000. Methods: Cases of cryptorchidism and hypospadias were identified from northern region hospital episodes statistics (HES). Trends in birth prevalence, based on the number of male live births, were assessed using linear regression. Results: Prevalence was 7.6 per 1000 male live births for cryptorchidism and 3.1 per 1000 male live births for hypospadias. The orchidopexy rates for 0–4 year olds and 5–14 year olds were 1.8 and 0.8 per 1000 male population, respectively. The rates for hypospadias repair for 0–4 year olds and 5–14 year olds were 0.6 and 0.1 per 1000 male population, respectively. There was a statistically significant decreasing temporal trend for the corrective procedure in cryptorchidism of 0.1 per 1000 male population aged under 5 years per annum (95% confidence interval: −0.01 to −0.05, p<0.001), but no temporal change for the corrective procedure in hypospadias (p = 0.60). Conclusion: HES data were of high quality for the study period. There was no significant change in the prevalence of surgically corrected hypospadias. However, there was an apparent decline in the prevalence of surgically corrected cryptorchidism that may reflect a decrease in the prevalence of the condition or may be due to a decrease in the rate of surgical intervention.